2022
DOI: 10.21037/tau-22-465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic kidney disease on cognitive function and α-klotho expression in hippocampus

Abstract: Background: Alpha-klotho (α-KL) is not only related to the regulation of calcium-phosphorus metabolism, and fibrosis in chronic kidney disease (CKD), it is also involved in the regulation of many cognitive disorders.We conducted this study to investigate the effects of CKD on cognitive dysfunction and α-KL.Methods: Doxorubicin was used to induce a CKD model, which was validated by weight, 24-hour urine protein quantification, serum creatinine (Cr), blood urea nitrogen (BUN), and kidney hematoxylin-eosin (HE) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(43 reference statements)
2
1
0
Order By: Relevance
“…All of these changes were improved in quercetin and/or vitamin D3 treated groups. In line with our result, Huang et al [26] noted in their study that the CKD group had hippocampus structural alterations, neuronal degeneration, and necrosis. Also, Ruiz et al [27] found that apoptosis of hippocampal neurons was observed in uremic animal models.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All of these changes were improved in quercetin and/or vitamin D3 treated groups. In line with our result, Huang et al [26] noted in their study that the CKD group had hippocampus structural alterations, neuronal degeneration, and necrosis. Also, Ruiz et al [27] found that apoptosis of hippocampal neurons was observed in uremic animal models.…”
Section: Discussionsupporting
confidence: 93%
“…Correspondingly, other investigations have agreed with our findings showing that the pathogenesis and development of CKD are associated with Klotho downregulations in animal models [3,34]. In addition, Huang et al [26] reported that since α klotho expression appears to have an impact on the cognition of CKD rats, it could be a useful target for the prevention and therapy of impaired cognitive functions linked to CKD. Interestingly, Klotho expression level was significantly increased in the quercetin group in Bhatiya et al [35] study, which is in line with our finding.…”
Section: Discussionsupporting
confidence: 92%
“…The variation in Klotho gene is associated with bigger brain volume and better cognitive function in older adults ( 52 ). In CKD rats, the expression of α-Klotho significantly declined in the hippocampus, which might affect the cognitive function ( 53 ). Furthermore, elevating Klotho in mice enhanced synaptic plasticity, enriched synaptic receptor subunit for learning and memory, and intrinsic connectivity in fronto-parietal ( 20 , 54 ).…”
Section: Discussionmentioning
confidence: 99%